Genetic Pedigree Analysis of the Pilot Breeding Program for the Rediscovered Galapagos Giant Tortoise from Floreana Island. (27th February 2018) - Miller, Joshua M; Quinzin, Maud C; Scheibe, Elizabeth H; Ciofi, Claudio; Villalva, Fredy; Tapia, Washington; Caccone, Adalgisa
Abstract: An aim of many captive breeding programs is to increase population sizes for reintroduction and establishment of self-sustaining wild populations. Genetic analyses play a critical role in these programs: monitoring genetic variation, identifying the origin of individuals, and assigning parentage to track family sizes. Here, we use genetic pedigree analyses to examine 3 seasons of a pilot breeding program for the Floreana island Galapagos giant tortoise, C. niger, that had been declared extinct for 150 years until individuals with mixed ancestry were recently discovered. We determined that 8 of 9 founding individuals were assigned parentage to at least 1 of 130 offspring produced, though there was considerable reproductive skew. In addition, we observed that genetic diversity of the progeny was lower than that of the founders. Despite the observed reproductive skew, we did not see evidence for assortative mating based on relatedness, but there was a trend toward reduced fitness when more related individuals bred. Finally, we found that the majority of progeny had ancestry assigned to the Floreana species (mean ± SE = 0.51 ± 0.02), though individual estimates varied. The success of these pilot seasons bodes well for a larger breeding program to help restore the previously extinct tortoise from Floreana island. Future efforts should continue to monitor for reproductive skew and assortative mating to maintain allelic diversity. We would also recommend forming smaller breeding groups and rotating individuals among them to prevent long-term reproductive skew among pairs.